2014
DOI: 10.1097/wco.0000000000000105
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial hypotension

Abstract: Clinical presentation as well as diagnostic and therapeutic approaches in intracranial hypotension are very heterogenous.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 103 publications
0
24
0
Order By: Relevance
“…Although SIH due to CSF leakage at C1-2 is less frequent than leakage occurring in the lower cervical or thoracolumbar spine,[14] it poses both diagnostic and therapeutic challenges to spine surgeons. With regard to diagnosis, it has been reported that extradural CSF collection at C1-2 on conventional CT myelography or MRI may often be a false localizing sign;[1019] CSF leakage from the dura of the lower cervical spine may move upward.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although SIH due to CSF leakage at C1-2 is less frequent than leakage occurring in the lower cervical or thoracolumbar spine,[14] it poses both diagnostic and therapeutic challenges to spine surgeons. With regard to diagnosis, it has been reported that extradural CSF collection at C1-2 on conventional CT myelography or MRI may often be a false localizing sign;[1019] CSF leakage from the dura of the lower cervical spine may move upward.…”
Section: Discussionmentioning
confidence: 99%
“…The use of conventional blood patch therapy administered from the lower lumbar spine may not be effective,[14] considering the long distance between the lower lumbar and upper cervical spine. Furthermore, the risk of vascular and neural injury associated with percutaneous puncture at C1-2 may not be negligible, considering its anatomical complexity and proximity to the brainstem.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spontaneous intracranial hypotension (SIH) is a syndrome in which hypovolemia of the cerebrospinal fluid (CSF) results in various symptoms [ 1 , 2 , 3 ]. The progression of symptoms is usually gradual and most patients seek medical attention complaining of chronic orthostatic headaches [ 1 , 2 , 3 ]. Although rare, patients may sustain a rapid neurologic deterioration and are brought to an emergency department [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although rare, patients may sustain a rapid neurologic deterioration and are brought to an emergency department [ 4 , 5 , 6 ]. On imaging studies, the great majority of those presenting with an altered mental status exhibit a bilateral accumulation of subdural fluid or hematoma, which is an important diagnostic clue [ 3 , 4 , 5 ]. However, when SIH-related subdural hematoma is only present unilaterally with a concomitant midline shift, diagnosing SIH may be difficult and inadvertent hematoma evacuation may result in further neurologic deterioration.…”
Section: Introductionmentioning
confidence: 99%